MARKETING DISTANCE WORK AT RELOCKED ENTERPRISES: CHALLENGES AND PROSPECTS - NEBYLYTSIA, Olena (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The study explores the distinctive aspects of managing marketing processes in enterprises that have undergone relocation due to wartime disruptions and economic instability, with a focus on the transition of marketing departments to remote operations. It highlights the concept of business relocation and its influence on the development of marketing strategies. The paper reviews contemporary frameworks for digital marketing management such as customer-centric approaches, data-driven decision-making, Agile methodologies, Integrated Marketing Communications (IMC), and omnichannel models. It also identifies essential digital tools that support analytics, automate communication, and ensure a consistent customer journey. Furthermore, the article addresses the core challenges faced by relocated enterprises—including logistical, legal, human capital, marketing, financial, and reputational issues—and offers practical recommendations for enhancing the efficiency of remote marketing teams while boosting the overall competitiveness of businesses in new market settings. This paper aims to explore the transformation of marketing management practices in relocated enterprises operating under war-related and economic disruptions. The study focuses on identifying how remote work formats reshape marketing strategies, tools, and organizational approaches, and highlights the ways in which digital solutions can support competitiveness and sustainable development in new market environments. The research employs a combination of systemic and comparative analysis, reviewing domestic and international experiences of business relocation and remote marketing management. Structural–logical methods are applied to systematize key managerial approaches such as customer-centric marketing, data-driven decision-making, Agile methodologies, Integrated Marketing Communications (IMC), and omnichannel strategies. Additionally, classification and synthesis are used to define the role of digital instruments including CRM platforms, business intelligence systems, and marketing automation tools. The findings demonstrate that relocation significantly intensifies the dependence of enterprises on digital technologies for maintaining business continuity. Among the major challenges identified are logistical constraints, workforce restructuring, legal and regulatory barriers, and the necessity of brand repositioning in unfamiliar cultural and consumer contexts. The analysis confirms that the effective use of online channels—social media, targeted advertising, analytics, content marketing, and e-commerce platforms—enables companies to ensure continuous communication with customers, build trust, and accelerate market entry. A particular emphasis is placed on the integration of digital touchpoints to provide a seamless customer experience across markets. Business relocation acts as both a stress test and a catalyst for marketing transformation. Remote marketing management, supported by digital technologies and flexible methodologies, is not merely a temporary adjustment but a strategic advantage. The study concludes that investment in digital infrastructure, the enhancement of employees’ digital competences, and the development of hybrid collaboration models are essential for the success of relocated enterprises. Properly managed, relocation can shift from being a survival mechanism to becoming an opportunity for strengthening competitiveness and achieving long-term growth in new economic environments.
Keywords: communication; competitiveness; digital tools; marketing; marketing activities; omnicanal strategy; organization; relocation